Point of care biliary ultrasound in the emergency department (BUSED) predicts final surgical management decisions. Issue 1 (2nd September 2022) - Hilsden, Richard; Mitrou, Nicholas; Hawel, Jeff; Leeper, Rob; Thompson, Drew; Myslik, Frank
Abstract : Objectives: Gallstone disease is a common reason for emergency department (ED) presentation. Surgeons often prefer radiology department ultrasound (RUS) over point of care ultrasound (POCUS) because of perceived of unreliability. Our study was designed to test the hypothesis that POCUS is sufficient to guide the management of surgeons treating select cases of biliary disease as compared to RUS. Methods: This was a prospective cohort study. Patients who presented to the ED with abdominal pain and findings of biliary disease on POCUS were included. The surgeon was then presented the case with POCUS only and recorded their management decision. Patients then proceeded to RUS, were followed through their stay, and analysis was performed to analyze the proportion of patients where the introduction of the RUS changed the management plan. Results: 100 patients were included in this study, and all received both POCUS and RUS. Depending on the surgeons' POCUS based management decisions, the patients were divided into three groups: (1) surgery, (2) duct clearance, (3) no surgery. Total bilirubin was 34±22 mmol/L in the duct clearance group vs 8.4±6.5 mmol/L and 16±12 mmol/L in the surgery and no surgery groups, respectively (p<0.05). POCUS results showed 68 patients would have been offered surgery, 21 offered duct clearance, and 11 no surgery. In 90% of cases, the introduction of RUS did not change management. The acute care surgeons elected to operate on patients more frequently than other surgical subspecialties (p<0.05). Conclusions: This study showed that fewer than 10% of patients with biliary disease seen on POCUS had a change in surgical decision-making based on the addition of RUS imaging. In uncomplicated cases of biliary disease, relying on POCUS imaging for surgical decision-making has the potential to improve patient flow. Level of evidence: II Prospective Cohort Study.